Risk acceptance criterion for tanker oil spill risk reduction measures - Psarros, George; Skjong, Rolf; Vanem, Erik (Marine pollution bulletin, 2011)
► Cost-effectiveness consideration for evaluating measures from accidental tanker oil spills. ► Updating the Cost of Averting a Tonne of oil Spilt (CATS) criterion. ► Probabilistic modelling of oil spill costs (log-normal). This paper is aimed at investigating whether there is ample support for the view that the acceptance criterion for evaluating measures for prevention of oil spills from tankers should be based on cost-effectiveness considerations. One such criterion can be reflected by the Cost of Averting a Tonne of oil Spilt (CATS) whereas its target value is updated by elaborating the inherent uncertainties of oil spill costs and establishing a value for the criterion’s assurance factor. To this end, a value of $80,000/t is proposed as a sensible CATS criterion and the proposed value for the assurance factor F=1.5 is supported by the retrieved Protection and Indemnity (P&I) Clubs’ Annual Reports. It is envisaged that this criterion would allow the conversion of direct and indirect costs into a non-market value for the optimal allocation of resources between the various parties investing in shipping. A review of previous cost estimation models on oil spills is presented and a probability distribution (log-normal) is fitted on the available oil spill cost data, where it should be made abundantly clear that the mean value of the distribution is used for deriving the updated CATS criterion value. However, the difference between the initial and the updated CATS criterion in the percentiles of the distribution is small. It is found through the current analysis that results are partly lower than the predicted values from the published estimation models. The costs are also found to depend on the type of accident, which is in agreement with the results of previous studies. Other proposals on acceptance criteria are reviewed and it is asserted that the CATS criterion can be considered as the best candidate. Evidence is provided that the CATS approach is practical and meaningful by including examples of successful applications in actual risk assessments. Finally, it is suggested that the criterion may be refined subject to more readily available cost data and experience gained from future decisions.